Piecewise Parallel Optimal Algorithm - Zhu, Zheng Hong (IntechOpen, 2018)
This chapter studies a new optimal algorithm that can be implemented in a piecewise parallel manner onboard spacecraft, where the capacity of onboard computers is limited. The proposed algorithm contains two phases. The predicting phase deals with the open-loop state trajectory optimization with simplified system model and evenly discretized time interval of the state trajectory. The tracking phase concerns the closed-loop optimal tracking control for the optimal reference trajectory with full system model subject to real space perturbations. The finite receding horizon control method is used in the tracking program. The optimal control problems in both programs are solved by a direct collocation method based on the discretized Hermite–Simpson method with coincident nodes. By considering the convergence of system error, the current closed-loop control tracking interval and next open-loop control predicting interval are processed simultaneously. Two cases are simulated with the proposed algorithm to validate the effectiveness of proposed algorithm. The numerical results show that the proposed parallel optimal algorithm is very effective in dealing with the optimal control problems for complex nonlinear dynamic systems in aerospace engineering area.